2021
DOI: 10.2147/phmt.s295378
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices of Parents About Immunization of Infants and Its Associated Factors in Wadla Woreda, North East Ethiopia, 2019

Abstract: Introduction: Improving infant immunization coverage and timeliness is a key health policy objective in many developing countries such as Ethiopia. Despite this, full immunization coverage in Ethiopia becomes low with the concurrent significant burden of vaccine-preventable diseases among infants. A previously published study acknowledged that parental knowledge, attitude, and practice towards infant immunization are vital issues to improve coverage and influence uptake. Objective: To assess parents' knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 32 publications
9
21
2
2
Order By: Relevance
“…It was found that the average knowledge score of the respondents in regard to childhood vaccination was good at 7.22±1.30 with an overall correct rate of 80.23%. This finding is similar with the results of two previous studies that were conducted in Saudi Arabia and North East Ethiopia, 31 , 32 which confirmed that respondents have good knowledge of childhood vaccination, know the importance of giving complete vaccinations to their children, and understand that vaccination is not harmful. Another similarity from these studies is the results highlighted positive correlations between parents’ level of education and occupational status with their knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was found that the average knowledge score of the respondents in regard to childhood vaccination was good at 7.22±1.30 with an overall correct rate of 80.23%. This finding is similar with the results of two previous studies that were conducted in Saudi Arabia and North East Ethiopia, 31 , 32 which confirmed that respondents have good knowledge of childhood vaccination, know the importance of giving complete vaccinations to their children, and understand that vaccination is not harmful. Another similarity from these studies is the results highlighted positive correlations between parents’ level of education and occupational status with their knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…34 , 35 This situation is relevant with the finding of three previous studies, which specifically highlighted that comprehensive information and guideline were still required by respondents who have positive attitudes towards childhood vaccinations. 31 , 32 , 36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to contradict the findings of Silveira et al [ 23 ], but our study did not evaluate the social-economic status of interviewed families. On the other hand, a study by Gebre Eyesus et al [ 24 ] indicated that parents who received immunization service more times were more likely to be knowledgeable about vaccines than parents who received the service only once. This might be attributed to the health education provided by healthcare professionals during the visits.…”
Section: Discussionmentioning
confidence: 99%
“…Ibu yang mempunyai sikap positif lebih banyak memberikan imunisasi dibandingkan dengan yang bersikao negatif. Lebih lanjut (Gebreyesus et al, 2021)menyimpulkan bahwa sikap orang tua berhubungan dengan pemberian imunisasi pada anak, yaitu 82,5% setuju untuk memberikan imunisasi lengkap pada anaknya.…”
Section: Sumber: Data Primerunclassified